Pentostatin, cyclophosphamide and rituximab for previously untreated advanced stage, low‐grade B‐cell lymphomas. (31st March 2015) - Samaniego, Felipe; Hagemeister, Fredrick; Romaguera, Jorge E.; Fanale, Michelle A.; Pro, Barbara; McLaughlin, Peter; Rodriguez, M. Alma; Neelapu, Sattva S.; Fayad, Luis; Younes, Anas; Feng, Lei; Berkova, Zuzana; et al.
Summary We conducted a prospective phase II trial of pentostatin, cyclophosphamide and rituximab as initial therapy for patients with previously untreated advanced stage low‐grade or indolent B‐cell lymphomas (iNHLs). Of 83 evaluable patients, 91·6% attained an overall response and 86·8% a complete or unconfirmed complete response. The 3‐year progression‐free survival (PFS) and overall survival rates were 73% and 93%, respectively. The 3‐year PFS rate was significantly different for different diagnoses (P = 0·01): 83% [95% confidence interval (CI): 0·72, 0·96] for follicular lymphomas, 73% (95% CI: 0·54, 1·0) for marginal zone lymphomas and 61% (95% CI: 0·46, 0·81) for small lymphocytic lymphomas. The most common adverse events were haematological. Of 509 cycles of chemotherapy administered, grade 3 or 4 neutropenia was reported in 68 cycles (13% of cycles administered) and most frequently occurred during cycles 4–6. This is the first report demonstrating the effectiveness of pentostatin, cyclophosphamide and rituximab in patients with previously untreated iNHLs, including those over 60 years of age.